Development of elastic design response spectra with emphasis on far‑source earthquakes for low to moderate seismic region - Nabilah, Abu Bakar; Raudhah, Ahmadi; Noor Sheena Herayani, Harith; Azlan, Adnan; Meldi, Suhatril (Springer Nature, 2023)
The development of design response spectra is crucial for earthquake design of structures. However, there are disagreements from the engineering community on the suitability of design values proposed by the existing design code which underestimates the long-period responses for fexible soils, typical of far-source earthquakes. This study uses soil response analysis to investigate the efect of near and far sources’ earthquakes on the response spectral acceleration of Malaysia in three seismically diferent regions, namely Peninsular Malaysia, Sabah and Sarawak. 1923 borehole data have been collected and analysed under 5 near and 4 far sources earthquakes, subjected to the intensity from the probabilistic seismic hazard analysis. The results show that for Peninsular Malaysia, the far-source earthquake will govern the response at a period of more than 1 s, indicating its importance for structures with long periods such as tall buildings. It is also found that the corner period TC is slightly higher than the code recommended and is dependent on the soil property, while TD is signifcantly higher for far-source earthquakes due to the larger magnitudes. The fnding of this research shows that the Eurocode 8 supplemented by the Malaysian National Annex (MS-EN1998-1, 2017) can be used to design structures in Malaysia, with some adjustments to the longer period motion for Peninsular Malaysia. Finally, it is recommended to perform an enhanced analysis for important structures of long periods to ensure their loadings are not underestimated.